HIGH FIELD 13C - NMR SPECTROSCOPIC ANALYSIS OF THE TRIACYLGLYCEROLS OF ADENOPUS BREVIFLORUS SEEDS OIL (Biological Sciences - PJSIR, 2004)
High resolution carbon - 13 NMR (gated decoupled) spectra of the carbonyl, saturated and olefinic carbons in Adenopus breviflorus seeds oil have been used for direct determination of the acyl composition and acyl positional distribution on the glycerol backbone. The spectra revealed the presence of saturated, oleic and linoleic fatty acids. Semi quantitative analysis using the integrals of the allylic carbons signals gave the percentage composition of the oil as saturated 25.00%, oleic 14.00% and linoleic 60.90%. These percentage compositions were confirmed by gas chromatography. The spectra further revealed that while the saturated fatty acids are distributed between the 1,3 (a) and 2 (b) glyceridic positions, oleic acid is attached only at the (a) glyceridic position while linoleic acid is attached mostly at the (b) glyceridic position.